2021
DOI: 10.3390/ijerph18126275
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Zika Virus and Other Recognized Flaviviruses among the Mosquito Vectors during and Post the Hajj Mass Gathering

Abstract: Makkah city, Kingdom of Saudi Arabia (KSA), contains many of the world’s mosquito vectors of parasitic and arboviral disease and is the site of the Hajj mass gathering. As such there is a risk of exportation and globalization of vector-borne viruses, including the re-emerging Zika virus (ZIKV). There was international concern regarding the introduction of ZIKV to KSA and potential international spread of the virus following the 2016 Hajj which took place few days after the Rio summer Olympics at the height of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…A. aegypti and A. albopictus are commonly infected with ISVs ( Supplementary Figure 2 and Supplementary Table 1 ) (Hoshino et al, 2009 ; Rizzo et al, 2014 ; Vasilakis et al, 2014 ; Chandler et al, 2015 ; Fan et al, 2016 ; Fernandes et al, 2016 ; Sadeghi et al, 2017 ; Ajamma et al, 2018 ; Fang et al, 2018 , 2021a , b ; Iwashita et al, 2018 ; Parry et al, 2018 , 2021 ; Zakrzewski et al, 2018 ; Zhang et al, 2018 ; Gravina et al, 2019 ; Martin et al, 2019 , 2020 ; Shi et al, 2019 ; Baidaliuk et al, 2020 ; da Silva Ferreira et al, 2020 ; Diagne et al, 2020 ; Jeffries et al, 2020 ; Kubacki et al, 2020 ; Ramos-Nino et al, 2020 ; Ribeiro et al, 2020 ; Supriyono et al, 2020 ; Thannesberger et al, 2020 ; Batson et al, 2021 ; Chiuya et al, 2021 ; Hameed et al, 2021 ; He et al, 2021 ; Munivenkatappa et al, 2021 ; Nebbak et al, 2021 ; Yezli et al, 2021 ; Calle-Tobón et al, 2022 ; Coatsworth et al, 2022 ; Duarte et al, 2022 ; Oguzie et al, 2022 ; Palatini et al, 2022 ; Aragão et al, 2023 ; Bennouna et al, 2023 ) that may alter their vectorial competence (Bolling et al, 2015 ; Öhlund et al, 2019 ). Phasi Charoen-like virus (PCLV) and Humaita Tubiacanga virus (HTV) are common ISVs found in A. aegypti , and A. albopictus ( Supplementary Figure 2 ).…”
Section: Mosquitoes and Arbovirusmentioning
confidence: 99%
“…A. aegypti and A. albopictus are commonly infected with ISVs ( Supplementary Figure 2 and Supplementary Table 1 ) (Hoshino et al, 2009 ; Rizzo et al, 2014 ; Vasilakis et al, 2014 ; Chandler et al, 2015 ; Fan et al, 2016 ; Fernandes et al, 2016 ; Sadeghi et al, 2017 ; Ajamma et al, 2018 ; Fang et al, 2018 , 2021a , b ; Iwashita et al, 2018 ; Parry et al, 2018 , 2021 ; Zakrzewski et al, 2018 ; Zhang et al, 2018 ; Gravina et al, 2019 ; Martin et al, 2019 , 2020 ; Shi et al, 2019 ; Baidaliuk et al, 2020 ; da Silva Ferreira et al, 2020 ; Diagne et al, 2020 ; Jeffries et al, 2020 ; Kubacki et al, 2020 ; Ramos-Nino et al, 2020 ; Ribeiro et al, 2020 ; Supriyono et al, 2020 ; Thannesberger et al, 2020 ; Batson et al, 2021 ; Chiuya et al, 2021 ; Hameed et al, 2021 ; He et al, 2021 ; Munivenkatappa et al, 2021 ; Nebbak et al, 2021 ; Yezli et al, 2021 ; Calle-Tobón et al, 2022 ; Coatsworth et al, 2022 ; Duarte et al, 2022 ; Oguzie et al, 2022 ; Palatini et al, 2022 ; Aragão et al, 2023 ; Bennouna et al, 2023 ) that may alter their vectorial competence (Bolling et al, 2015 ; Öhlund et al, 2019 ). Phasi Charoen-like virus (PCLV) and Humaita Tubiacanga virus (HTV) are common ISVs found in A. aegypti , and A. albopictus ( Supplementary Figure 2 ).…”
Section: Mosquitoes and Arbovirusmentioning
confidence: 99%
“…Furthermore, thermal cameras are installed at all borders. In a recent study, screening for summary, flaviviruses among mosquitoes in 2016 accomplished during Hajj period, and at the height of the zika virus epidemic was accomplished and no known flaviviruses were revealed, but possibly a novel type of flavivirus was detected ( Yesli et al, 2021 ). However, future studies are needed to investigate the novel mosquito virus identified.…”
Section: Other Infections Of Importancementioning
confidence: 99%